Performanc of the Yellowfin Tuna Kite Line Fishery Business in Lele Village, Mandioli Selatan District, South Halmahera Regency - Salim , Jamila Hi.; Karman, Amirul; Muksin, Darmiyati (Agrikan Jurnal Agribisnis Perikanan, 2025)
Fishermen in Lele Village, Mandioli Selatan District, South Halmahera Regency use kite line fishing gear to catch yellowfin tuna. Production inputs are factors that influence the increase in fishermen's catches. The use of effective and efficient production inputs will increase the production of catches and fishermen's income. Therefore, this study aims to evaluate the performance of the yellowfin tuna kite line fishery business which includes technical, biological, and economic aspects. The study was conducted from November to December 2023 in Lele Village, Mandioli Selatan District, South Halmahera Regency. The method used in the study was a descriptive survey method. The results of the study showed that the fishing gear used to catch yellowfin tuna by fishermen in Lele Village, Mandioli Selatan District, South Halmahera Regency was kite line. The trend in catch production increased from 2022 to 2023, while the productivity of the fishing fleet for 5 years (2019-2023) increased. This fishery business is profitable and worth continuing. The average investment cost of the yellowfin tuna kite line fishery business is IDR. 80,015,000.00, average production value of Rp. 864,205,920.00/year, average operational cost of IDR. 742,885,714.29/year, average profit of IDR. 106,500,920.00/year, Average NPV value of IDR. 81,708,384.47, average Net B/C ratio of 1.02, average IRR value of 32.43%, average BEP value of IDR. 755,853,658.10, and average PP value of 0.76 years.